Impact of Obesity and Hyperglycemia on Placental Mitochondria. (14th August 2018) - Mandò, Chiara; Anelli, Gaia Maria; Novielli, Chiara; Panina-Bordignon, Paola; Massari, Maddalena; Mazzocco, Martina Ilaria; Cetin, Irene
Abstract : A lipotoxic placental environment is recognized in maternal obesity, with increased inflammation and oxidative stress. These changes might alter mitochondrial function, with excessive production of reactive oxygen species, in a vicious cycle leading to placental dysfunction and impaired pregnancy outcomes. Here, we hypothesize that maternal pregestational body mass index (BMI) and glycemic levels can alter placental mitochondria. We measured mitochondrial DNA (mtDNA, real-time PCR) and morphology (electron microscopy) in placentas of forty-seven singleton pregnancies at elective cesarean section. Thirty-seven women were normoglycemic: twenty-one normal-weight women, NW, and sixteen obese women, OB/GDM(−). Ten obese women had gestational diabetes mellitus, OB/GDM(+). OB/GDM(−) presented higher mtDNA levels versus NW, suggesting increased mitochondrial biogenesis in the normoglycemic obese group. These mitochondria showed similar morphology to NW. On the contrary, in OB/GDM(+), mtDNA was not significantly increased versus NW. Nevertheless, mitochondria showed morphological abnormalities, indicating impaired functionality. The metabolic response of the placenta to impairment in obese pregnancies can possibly vary depending on several parameters, resulting in opposite strains acting when insulin resistance of GDM occurs in the obese environment, characterized by inflammation and oxidative stress. Therefore, mitochondrial alterations represent a feature of obese pregnancies with changes in placental energetics that possibly can affect pregnancy outcomes.